2013
DOI: 10.1111/1467-9248.12076
|View full text |Cite
|
Sign up to set email alerts
|

Blame and Punishment? The Electoral Politics of Extreme Austerity in Greece

Abstract: (150 words)Can governments that introduce extreme austerity measures survive elections? Contrary to economic voting expectations, the PASOK government in Greece initially appeared to cope quite well, claiming victory in regional elections in 2010 despite widespread anti-austerity protest. In this paper, we interpret this result with the help of a post-election survey, which also covered future voting intention. The explanatory power of models based on theories of economic voting and blame attribution as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 52 publications
(62 reference statements)
1
15
0
1
Order By: Relevance
“…In all, as Greece plunged into the most severe national economic crisis in the eurozone, a political crisis unfolded as well. This manifested in various ways, including an upsurge in electoral volatility, transformative party system realignments, fierce political debates in parliament, problems in government formation, the emergence of new social movements, and mass protests and strikes (Karyotis & Rüdig 2015).…”
Section: The Greek and Cypriot Far Right In Contextmentioning
confidence: 99%
“…In all, as Greece plunged into the most severe national economic crisis in the eurozone, a political crisis unfolded as well. This manifested in various ways, including an upsurge in electoral volatility, transformative party system realignments, fierce political debates in parliament, problems in government formation, the emergence of new social movements, and mass protests and strikes (Karyotis & Rüdig 2015).…”
Section: The Greek and Cypriot Far Right In Contextmentioning
confidence: 99%
“…Campbell et al 1960). Moreover, simple materialist arguments are vulnerable to the 'securitization' discourse of the government, a discourse that claims inability to eschew austerity in the face of existential threats to the nation (Karyotis and Rüdig 2015).…”
Section: Impact On Public Opinionmentioning
confidence: 99%
“…With regard to political elites, Vasilopoulou et al (2014), examining parliamentary speeches from the period 2009-2011, found that while the leaders of the two parties of power blamed each other, and the minor opposition parties blamed them both, in addition all parties implicated external actors, including the EU. In the case of public opinion, a survey conducted in December 2010 found that 42% of respondents considered the EU shared in the responsibility compared to 41% for the current and 64% for the previous Greek governments ( Karyotis and Rüdig, 2015). As Greece's economic situation worsened in the years following the first bailout in May 2010, there was an increasing tendency to differentiate between two distinct phases of the crisis.…”
Section: Linking the European And The Domesticmentioning
confidence: 99%